"Chef recommended" or "most popular"? Cultural differences in customer preference for recommendation labels. (April 2020) - Yang, Bi; Mattila, Anna S.
Highlights: Culture can affect customer preference for expertise-based versus popularity-based recommendations. Collectivists show a higher purchase intention when the recommendation reflects popularity (vs. expertise). Individualists show a lower purchase intention when the recommendation reflects popularity (vs. expertise). Self-construal is the underlying mechanism explaining the culture effect for popularity cues. Abstract: Despite the widespread use of recommendation labels on restaurant menus, no prior research has investigated their impact on diners' menu decisions. To bridge that gap, this study examines the joint effect of recommendation type (chef recommended vs. most popular) and culture (individualistic vs. collectivistic) on diners' purchase intention. The results indicate that Indians showed higher levels of purchase intention when the recommendation involved a popularity (vs. expertise) cue, while Americans responded more favorably to an expertise (vs. popularity) cue. Furthermore, this study demonstrates that self-construal is the underlying mechanism explaining the culture effect for popularity cues. Theoretical and managerial implications are discussed.